Occurrence of the red giant flying squirrel (Petaurista petaurista: Sciuridae) in Bangladesh - Kabir, M. Tarik; Ahsan, M. Farid; Khatoon, Ayesha; Rahman, M. Mizanur (Nature Conservation Research: Заповедная наука, 2018)
This report confirms the presence of the red giant flying squirrel Petaurista petaurista from the Idgarh Reserve Forest in Cox's Bazar (North) Forest Division in the southern part of Bangladesh. The chestnut-red dorsal body colour, white ventral surface, large and flesh-coloured nostrils, and gray long tail with blackish tip confirm the observed species as a red giant flying squirrel. Long-term monitoring, habitat protection and its ecology need to be studied for initiating further steps to conserve it in Bangladesh.